2021
DOI: 10.1186/s12877-021-02608-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between biomarkers of bone health and osteosarcopenia among Iranian older people: The Bushehr Elderly Health (BEH) program

Abstract: Background Osteosarcopenia is referred to as co-incidence of osteoporosis/osteopenia and sarcopenia which is defined as a geriatric syndrome with a significant prevalence that increases morbidity and mortality. There are some relevant factors that can show an increased risk of incidence of osteosarcopenia. Aim We aimed to consider the association of bone turnover markers such as Osteocalcin (OC), C-terminal cross-linked telopeptide (CTX), Tartrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Additionally, the biochemical assessment of bone and muscle metabolism has been proposed to improve early diagnosis and screening, and assess the response to therapies in people with OS. Fathi and colleagues [ 29 ] investigated the association of bone turnover markers such as osteocalcin (OC), C-terminal cross-linked telopeptide (CTX), tartrate-resistant acid phosphatase (TRAP), alkaline phosphatase bone (BALP), and other factors such as vitamin D, calcium, phosphorus, and alkaline phosphatase with OS in 400 elderly people. The study results showed a statistically significant difference in OC, CTX, and TRAP between osteosarcopenia (−) and osteosarcopenia (+) people.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Additionally, the biochemical assessment of bone and muscle metabolism has been proposed to improve early diagnosis and screening, and assess the response to therapies in people with OS. Fathi and colleagues [ 29 ] investigated the association of bone turnover markers such as osteocalcin (OC), C-terminal cross-linked telopeptide (CTX), tartrate-resistant acid phosphatase (TRAP), alkaline phosphatase bone (BALP), and other factors such as vitamin D, calcium, phosphorus, and alkaline phosphatase with OS in 400 elderly people. The study results showed a statistically significant difference in OC, CTX, and TRAP between osteosarcopenia (−) and osteosarcopenia (+) people.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…The high prevalence of DS in this Iranian elderly community shows the importance of conducting such studies and implementing relevant interventions to address contributory factors. Also in these subjects we found a higher risk of osteosarcopenia, risk of falls and fractures [ 56 ]. This study examined a large sample of older people in Iran using an established protocol, including that we evaluated both measured body composition indices of different anthropometric indices and DXA with standard methods.…”
Section: Discussionmentioning
confidence: 99%
“…These indicators, including ALP, TRAP, OC, OCIF, ODF, have been previously reported to play crucial roles in bone remodeling. 38 For example, ALP and TRAP are markers of osteoblast and osteoclast activity, respectively, while OC is a marker of bone formation. Therefore, their abnormal expression may contribute to the development of OFs by disrupting the balance of bone remodeling.…”
Section: Discussionmentioning
confidence: 99%